Finance and Economic Opportunity - Demirgüç-Kunt, Asli; Levine, Ross (World Bank, Washington, DC, 2012)
An influential body of theoretical research and an emerging line of empirical work suggest that the operation of the formal financial system affects the degree to which economic opportunities are defined by talent and initiative rather than by parental wealth and social connections. This paper discusses the theory of how financial markets influence economic opportunity and reviews recent empirical work on the relation between formal financial systems and poverty, income inequality, and economic opportunity. The authors consider recent efforts to measure the ability of households and small enterprises to access financial services, the impact of this access, and the mechanisms through which finance affects poverty and inequality. The authors argue that considerably more research is needed to identify which formal financial sector policies enhance the operation of the financial system in ways that expand the economic horizons of the economically disenfranchised.